Training and Support for Hybrid Closed-Loop Therapy. (January 2022) - Boughton, Charlotte K.; Hartnell, Sara; Allen, Janet M.; Fuchs, Julia; Hovorka, Roman
Hybrid closed-loop therapy is an emerging technology transforming the management of type 1 diabetes (T1D). Research studies demonstrate glycemic and quality of life benefits of hybrid closed-loop therapy for people with T1D. Translating these outcomes into standard clinical practice is critical for reimbursement and improving access to this technology. High-quality training is essential for achieving optimal outcomes with hybrid closed-loop therapy. Basic diabetes skills and tasks are as important, or even more important, with closed-loop therapy than with standard insulin therapy and need to be reiterated. Establishing expectations of hybrid closed-loop therapy clearly at the outset promotes long-term usage and optimal outcomes. We share key aspects of training and support for users of commercially available hybrid closed-loop systems and consider who may benefit from this technology.